2019
DOI: 10.1111/jfpp.14061
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the effect of chilling on selected attributes of fresh pork

Abstract: The objective of this study was to examine the effect of accelerated chilling on ultimate pH (pH u ), drip loss, color (L*a*b*), and Warner-Bratzler shear force (WBSF) of fresh pork using a meta-analytical approach. Additionally, two subgroups differentiated by stunning method (electrical vs. CO 2 ) were included. The meta-analysis shown that accelerated chilling has an ability to improve quality of fresh pork, however, not all benefits were obviously evident. The overall effects with no overlapping zero CI pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Variation in post-mortem metabolites did, however, explain why variation in pH and temperature occurred. Additionally, mechanisms that control pork quality development are associated not only with post-mortem muscle metabolism, but also with the chilling and stunning method (Zybert et al, 2019), transportation and stress (Henckel et al, 2002;Hambrecht et al, 2005), and variations in temperature (combination of high temperature and low pH appears as pale, soft, exudative meat (Pearson & Young, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Variation in post-mortem metabolites did, however, explain why variation in pH and temperature occurred. Additionally, mechanisms that control pork quality development are associated not only with post-mortem muscle metabolism, but also with the chilling and stunning method (Zybert et al, 2019), transportation and stress (Henckel et al, 2002;Hambrecht et al, 2005), and variations in temperature (combination of high temperature and low pH appears as pale, soft, exudative meat (Pearson & Young, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in heat removal from carcasses, coupled with temperature decline in muscles, prevents the formation of inherent pork due to a decrease in the rate and extent of post-mortem metabolism and pH decline [ 64 , 67 , 68 , 69 , 70 ]. The accelerated chilling, in comparison to conventional chilling, has an ability to decrease the relative rate of pH decline and increase ultimate pH [ 26 , 69 , 70 ]. Nonetheless, the sub-group meta-analysis indicated that the chilling method had no effect on variability in pH u between ES and CO 2 -stunned pigs.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup also held medium heterogeneity. Some studies have shown that accelerated air chilling has the potential to decrease drip loss [ 26 , 69 , 78 , 79 , 80 ]. The chilling-dependent mechanism controlling water distribution and mobility in muscles is associated with the effect of temperature on post-mortem metabolism and temperature-induced structural changes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drip loss is an index to show muscle to hold inherent water, which demonstrates destabilization and disruption of muscle cell membranes, myofibrillar shrinkage, net charge effect, etc. [30]. The marinate processing of the marinated pork might break the native structure of the pork muscle, and this may lead to the drip loss of the marinated pork being higher than those of the control at 0 and 2 d. The protein degradation of the control was higher than that of the marinated pork, which might be the reason that the drip loss of the control was higher than that of the marinated pork at 4 and 6 d. To further confirm the protein degradation of the control and the marinated pork, the content of sulfhydryl, the soluble peptides, and the activity of Ca 2+ -ATPase were determined.…”
Section: Ph and Drip Lossmentioning
confidence: 99%